PERLINDUNGAN HUKUM BAGI DEBITUR BANK MENURUT PERATURAN PERUNDANG-UNDANGAN DI INDONESIA [Legal Protection for Bank Debtors According to the Laws and Regulations in Indonesia] - Sahat Marulitua Sihombing (Fakultas Hukum, Universitas Pelita Harapan | Lippo Karawaci, Tangerang, 2021)
The main activity of commercial banks is providing credit. In providing credit, banks are required to make a careful assessment of the business feasibility of a debtor, by applying the Prudent Banking Principle and Know Your Customer (KYC) Principle. The legal relationship between a bank and a debtor customer is based on an agreement, where the relationship must be based on an agreement and the principle of balance between the two parties. Because the bank as the creditor wants the credit to be returned by the debtor as agreed, the bank becomes dominant in determining the terms of credit, including in designing the substance of the credit agreement. This article will analyze the extent of legal protection for bank debtors according to the laws and regulations in Indonesia. The research is normative juridical method, the legal materials used consist of primary legal materials in the form of laws and derivative regulations, secondary legal materials in the form of books and journals in the field of law, and tertiary legal materials in the form of law dictionaries and encyclopedias. The data used in this research is secondary data. The results show that normative statutory regulations contain legal protection for debtor customers, but in reality, because banks need security for their credit repayments, the clause in the credit agreement does not pay attention to the principle of balance and does not accommodate the rights of the debtor. It is the bank that dominates the design of the credit agreement and as a result, the substance is made more in favor of the bank. The debtor is in a position that must accept the contents of the agreement because he really needs credit, and the debtor has no other choice.Bahasa Indonesia Abstrak: Kegiatan utama bank umum adalah memberikan kredit. Dalam memberikan kredit, bank wajib melakukan penilaian yang seksama atas kelayakan usaha debitur, dengan menerapkan Prudent Banking Principle dan Know Your Customer (KYC) Principle. Hubungan hukum antara bank dengan nasabah debitur didasarkan pada perjanjian, di mana hubungan dimaksud harus didasari kata sepakat dan adanya asas keseimbangan di antara kedua belah pihak. Karena bank sebagai kreditur menginginkan agar kredit dapat dikembalikan debitur sesuai dengan yang diperjanjikan, bank menjadi dominan dalam menentukan syarat-syarat kredit termasuk dalam merancang substansi perjanjian kreditnya. Artikel ini akan menganalisis sejauh mana perlindungan hukum bagi debitur bank menurut peraturan perundang-undangan di Indonesia. Penelitian yang dilakukan bersifat yuridis normatif. Adapun bahan hukum yang dipergunakan terdiri dari bahan hukum primer berupa undang-undang dan peraturan turunannya, bahan hukum sekunder berupa buku-buku dan jurnal di bidang hukum, dan bahan hukum tersier berupa kamus dan ensiklopedia hukum. Data yang dipergunakan dalam penelitian ini adalah data sekunder. Hasil penelitian menunjukkan bahwa peraturan perundang-undangan secara normatif telah memuat perlindungan hukum bagi nasabah debitur, namun dalam kenyataannya karena bank memerlukan keamanan atas pengembalian kreditnya, klausula dalam perjanjian kredit kurang memperhatikan asas keseimbangan dan kurang mengakomodasi hak-hak debitur. Pihak bank lah yang dominan mendisain perjanjian kredit dan sebagai akibatnya, substansinya dibuat lebih banyak memihak bank. Debitur berada pada posisi yang harus menerima isi perjanjian dimaksud karena dia sangat membutuhkan kredit, dan debitur tidak mempunyai pilihan lain.